Identificação das causas da eflorescência nas residências de Caraúbas-RN: estudo de caso - Oliveira Junior, Fernando Antônio Serra de (Universidade Federal Rural do Semi-Árido, 2018)
Efflorescence is defined as crystalline deposits, generally of white color, that appear on the surface of the revetment, such as walls and ceiling, through the migration and subsequent evaporation of saline aqueous solutions. Known popularly as saltpeter, efflorescence is part of a group of pathological manifestations that cause aesthetic and structural damages in more advanced cases. The objective of this work was to identify the consequences of the damages caused by the efflorescence in two districts of the city of the Caraúbas-RN residences. For the preliminary analysis of the efflorescence in the city of Caraúbas, visits were made to the residences to obtain information about the damages caused by nitrate and questionnaire application. To obtain an indication of the amount of salts contained in the building materials available in the local market, an electrical conductivity test was performed and the following civil construction inputs: river sand, beach sand, massive ceramic and hollow bricks, ceramic tile, gravel-0, in addition to water from the city's supply system. It was verified that the inputs of the civil construction used in the city of Caraúbas come from different regions. About 92% of respondents have tried, at least once, some measure of correction against saltpeter; a total of 25% have already done a repair in their residences because of the harmful effects of efflorescence and subflorescence, while approximately 17% have already made more than one repair. From the electrical conductivity test, it was possible to conclude that most of the inputs do not present a very high electrical conductivity value, except in the case of common brick, which presented a value of 22.685 mS / cm, well above 6.0, which is already considered extreme.
Monografia
Keywords: Condutividade elétrica; Eflorescência e sais solúveis.; CIENCIAS EXATAS E DA TERRA::CIENCIA E TECNOLOGIA